2021
DOI: 10.1007/s00432-021-03779-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression of prognostic genes in primary melanoma and benign nevi

Abstract: Purpose To evaluate the protein expression characteristics of genes employed in a recently introduced prognostic gene expression assay for patients with cutaneous melanoma (CM). Methods We studied 37 patients with CM and 10 with benign (melanocytic) nevi (BN). Immunohistochemistry of primary tumor tissue was performed for eight proteins: COL6A6, DCD, GBP4, KLHL41, KRT9, PIP, SCGB1D2, SCGB2A2. Results The protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Based on these ndings, we identi ed ve prognostic signature genes for SKCM among the DEGs among the three molecular subgroups, namely FCGR2, GBP4, CHRDL1, SLC5A3 and GJA1. The expression level of guanylate-binding protein 4 gene (GBP4) has been shown in a previous study increased in melanoma tissue, which is consistent with our experiment 25 . Gap junction protein alpha 1 gene (GJA1), also called connexin 43 (Cx43), has a tumor suppressor function and can inhibit the progression of melanoma 26 .…”
Section: Discussionsupporting
confidence: 93%
“…Based on these ndings, we identi ed ve prognostic signature genes for SKCM among the DEGs among the three molecular subgroups, namely FCGR2, GBP4, CHRDL1, SLC5A3 and GJA1. The expression level of guanylate-binding protein 4 gene (GBP4) has been shown in a previous study increased in melanoma tissue, which is consistent with our experiment 25 . Gap junction protein alpha 1 gene (GJA1), also called connexin 43 (Cx43), has a tumor suppressor function and can inhibit the progression of melanoma 26 .…”
Section: Discussionsupporting
confidence: 93%
“…Among the 15 genes considered in this signature, GMDS, SDF2L1, KLHL17, ITGB5, CAT3 and KLHL41 were previously found to be associated with tumors. For example, a mutation in GMDS was shown to induce the proliferation of colon cancer cells [ 16 ], SDF2L1 expression was found to be upregulated when nasopharyngeal carcinoma cell growth was promoted in vitro [ 17 ], KLHL17 was shown to be associated with prostate cancer [ 18 ], ITGB5 was considered to serve as a prognostic biomarker for poor prognosis in gastric cancer [ 19 ], and KLHL41 expression was found to be significantly enhanced in melanoma [ 20 ]. However, the present study is the first to show the association between the expression of these genes and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the GBP family is highly important for antibacterial defense and that Guanylate binding protein 4 (GBP4) is a key inflammasome adaptor required for prostaglandin biosynthesis and bacterial clearance by neutrophils (Wandel et al 2020 ; Tyrkalska et al 2016 ). GBP4 was also found to be highly expressed in multiple cancer types, including melanoma (Gambichler et al 2022 ) and colorectal cancer (Xu et al 2020 ). In another study, GBP4 expression was shown to be correlated with poor overall survival (OS) in patients with ovarian cancer (Huo et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%